2014
DOI: 10.1080/17450128.2014.954025
|View full text |Cite
|
Sign up to set email alerts
|

Home visiting programs for HIV-affected families: a comparison of service quality between volunteer-driven and paraprofessional models

Abstract: Home visiting is a popular component of programs for HIV-affected children in sub-Saharan Africa, but its implementation varies widely. While some home visitors are lay volunteers, other programs invest in more highly trained paraprofessional staff. This paper describes a study investigating whether additional investment in paraprofessional staffing translated into higher quality service delivery in one program context. Beneficiary children and caregivers at sites in KwaZulu-Natal, South Africa were interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…However, the intervention will need to be tailored to context. For example, this intervention was delivered in an urban setting and may require adaptation for implementation in rural settings where CHWs may have to travel longer distances in difficult terrain [ 36 ]. This is likely to have implications on the number of visits each CHW can conduct each day, the total number of successful visits each CHW can make, and the time spent travelling to each participant household by CHWs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the intervention will need to be tailored to context. For example, this intervention was delivered in an urban setting and may require adaptation for implementation in rural settings where CHWs may have to travel longer distances in difficult terrain [ 36 ]. This is likely to have implications on the number of visits each CHW can conduct each day, the total number of successful visits each CHW can make, and the time spent travelling to each participant household by CHWs.…”
Section: Discussionmentioning
confidence: 99%
“…The country’s community-based child and youth care workers (CYCWs) use the Isibindi model of care to serve vulnerable children around the country [ 1 ], with a principal focus on providing support to the more than 2 million children orphaned or otherwise affected by HIV and AIDS [ 2 ]. Services provided range from HIV prevention and healthcare referrals to psychological support, education assistance, child protection, linkages to social grants, and more [ 3 ]. Isibindi was formally developed in 2005 after related activities dating back to 2000, by the country’s National Association of Child Care Workers (NACCW).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that Isibindi programming is associated with positive outcomes for children and adolescents including increased access to social grants and basic material resources [ 3 , 5 ] as well as lower HIV risk behaviour [ 6 ]. Evidence from qualitative research, however, suggests that these results may come at a high personal cost to Isibindi CYCWs in South Africa, who report experiencing work-related stress, secondary trauma, difficult working conditions, and poor stakeholder relations [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the disparity in financial remuneration between the CHWs and the Change Agents emerged as a key tension in this case, both the research presented here, and the literature highlight that financial remuneration is not the sole motivation that individuals have for becoming community‐based healthcare workers (Akintola, ; Greenspan et al, ; Kidman, Nice, Taylor, & Thurman, ; Mwai et al, ; Pallas et al, ). A desire to learn, as well as to improve the lives of loved ones and the general health and well‐being of the community, are also key factors that motivate individuals to participate in such programmes.…”
Section: Discussionmentioning
confidence: 82%